From Brainstorming to Argumentation: Mind Mapping as Cognitive Scaffolding for Critical EFL Writing in Vocational Education - Sitti Hadijah; Muhammad Tahir; Vivit Rosmayanti; Andi Asrifan (STIT Buntet Pesantren Cirebon, 2026)
This study examined the function of mind mapping as cognitive scaffolding in improving critical thinking abilities and analytical exposition writing performance among vocational EFL students. The study examined the extent to which mind mapping techniques enhanced students' critical thinking and writing performance, as well as students' perceptions of the strategy's application during the writing process. A sequential explanatory mixed-methods design was utilized, comprising 34 eleventh-grade vocational students allocated into experimental and control groups. Quantitative data were gathered via pretest and posttest analytical exposition writing assignments evaluated using writing and critical thinking rubrics, and qualitative data were acquired through semi-structured interviews with chosen participants. The quantitative data were examined using descriptive statistics, paired sample t-tests, independent sample t-tests, and Cohen’s d effect size analysis, while the qualitative data were assessed by thematic analysis. The results indicated that students utilizing mind mapping techniques exhibited superior enhancement in critical thinking abilities and writing proficiency relative to those subjected to traditional teaching methods. Qualitative research revealed that mind mapping improved concept organization, persuasive reasoning, writing confidence, and classroom participation, although initial hurdles associated with brainstorming and time management. The findings indicate that mind mapping serves as an effective visual cognitive framework that enhances higher-order thinking and the development of argumentative writing in vocational EFL settings.